2018
DOI: 10.1111/exd.13532
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of FUCA1 knock‐down in keratinocytes reveals new insights into the pathogenesis of fucosidosis skin lesions

Abstract: Fucosidosis is a rare lysosomal storage disease which has been classified into two subtypes, depending on the severity of clinical signs and symptoms. Fucosidosis patients' skin abnormalities include angiokeratoma corporis diffusum, widespread telangiectasia, thick skin, hyperhidrosis and hypohidrosis, acrocyanosis and distal transverse nail bands. It has been described that >50% of fucosidosis patients have angiokeratoma. At molecular level, fucosidosis is caused by lysosomal alpha-L-fucosidase (FUCA1) gene m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…We were also able to capture downregulations of lysosomal enzymes such as FUCA1 and GALNS involved with keratinocyte differentiation, 34,35 and lipid biosynthesis/trafficking 48 . Also, we detected a decreased expression of AZGP which is correlated with abnormalities in lipid metabolism.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…We were also able to capture downregulations of lysosomal enzymes such as FUCA1 and GALNS involved with keratinocyte differentiation, 34,35 and lipid biosynthesis/trafficking 48 . Also, we detected a decreased expression of AZGP which is correlated with abnormalities in lipid metabolism.…”
Section: Discussionmentioning
confidence: 74%
“…We were able to detect even from non‐lesional AD, significant variation on lipid metabolism‐related enzymes compared with HCs. The cellular mediators, tissue alpha‐L‐fucosidase (FUCA1), zinc‐alpha‐2‐glycoprotein (AZGP) and N‐acetylgalactosamine‐6‐sulfatase (GALNS) have been found significantly downregulated in AD 34,35 . In particular, we assessed down‐expression of 7‐dehydrocholesterol reductase (DHCR7) and ester hydrolase (C11orf54).…”
Section: Resultsmentioning
confidence: 99%
“…We identified several proteins in MIH saliva associated with skin-abnormalities caused by chronic inflammation. For example, FUCA1 is a carbohydrate degrading enzyme and FUCA1 gene-mutations are linked to fucosidosis that causes severe skin abnormalities due to disturbed carbohydrate metabolism 55 . The human kallikrein 8 protein (KLK8) is expressed in many normal tissues including the salivary gland 56 .…”
Section: Discussionmentioning
confidence: 99%
“…Fucosidosis (OMIM, 230000) is a rare autosomal recessive LSD caused by the deficiency of the α-L-fucosidase enzyme (EC 3.2.1.51) coded by FUCA1 gene, that causes accumulation of glycopeptides such as fucosyl-glycopeptides and oligosaccharides in some tissues [150]. In Colombia, a study of Valero-Rubio et al [150] analyzed in keratinocytes the effect of FUCA1 gene knock-down to understand the pathogenesis in skin lesions that fucosidosis patients present. The authors found that 387 genes were deregulated among cells transfected with a siRNA-A targeting FUCA1 (222 upregulated and 165 downregulated).…”
Section: Fucosidosismentioning
confidence: 99%